Serological diagnostics in the detection of IgG autoantibodies against human collagen VII in epidermolysis bullosa acquisita: a multicentre analysis. (1st December 2017) - Schmidt, T.; Hoch, M.; Lotfi Jad, S.S.; Solimani, F.; Di Zenzo, G.; Marzano, A.V.; Goebeler, M.; Cozzani, E.; Kern, J.S.; Sitaru, C.; Lakoš Jukić, I.; Sárdy, M.; et al.
Summary: Background Epidermolysis bullosa acquisita (EBA) is a rare, potentially devastating autoimmune disease of the skin. IgG autoantibodies directed against type VII collagen (Col7), the major component of anchoring fibrils, induce skin fragility leading to cutaneous and mucocutaneous blister formation, which is mostly of a scarring phenotype. Thus, powerful and reproducible diagnostic assays are critical to establish the diagnosis of EBA early to avoid irreversible sequelae. Objectives The present international, retrospective multicentre study included a large cohort of patients with EBA and evaluated the diagnostic power of four different diagnostic assays for the detection of anti‐Col7 IgG autoantibodies. Methods Overall, 95 EBA sera and 200 control sera consisting of 100 bullous pemphigoid sera, 50 pemphigus vulgaris sera and 50 sera of healthy controls were tested for anti‐Col7 IgG autoantibodies using indirect immunofluorescence (IIF), two commercial enzyme‐linked immunosorbent assay (ELISA) systems and Western blot (WB) analysis. EBA sera were taken from patients with positive direct immunofluorescence and IgG reactivity in at least one of the immunoserological assays (IIF, ELISA, WB). Results A Col7‐NC1/NC2 ELISA (MBL, Nagoya, Japan) showed the highest sensitivity (97·9%), followed by a Col7‐NC1 ELISA (Euroimmun, Lübeck, Germany) (89·5%), WB with Col7‐NC1 (85·3%), and IIF on saline‐split human skin (74·7%). The specificities of both ELISA systems were comparable (NC1 98·7%, NC1/NC2 99·3%). Furthermore, WB was more sensitive than IIF, which was more specific. Conclusions The two commercially available ELISA systems allow for a highly sensitive and specific diagnosis of EBA. The sensitivity of the Col7‐NC1/NC2 ELISA is significantly higher compared with the ELISA based on the Col7‐NC1 domain only.